Drama Therapy Counseling as Mental Health Care of College Students - Chang, Wen-Lung (Int J Environ Res Public Health, 2019)
(1) Background: This study aims to apply drama therapy to a counseling group to address the mental health problems of college students in Taiwan due to the increasingly serious psychological problems that have happened in recent times. Based on the healing factors in drama therapy, we applied such therapy activities to four counseling groups composed of 12 high-risk students from Taiwan. (2) Methods: “Questionnaire-based assessment, participant self-assessment and participant attitude assessment” methods were used to evaluate the six mental health indicators of the participants in the evaluation of drama therapy’s effect and the groups’ pre-test and post-test (the first group and the last group). The six indicators were self-awareness, self-expression, interpersonal and communication skills, self-cognitive reconstruction ability, social role ability, and decision-making ability. Data were collected and assessed for the frequencies and percentages of each indicator item. Sets of paired-samples t-tests, independent t-tests, and two-way repeated measures ANOVAs were employed to evaluate the different designs. (3) Results: The results revealed that drama therapy could deliver significantly positive effects for and improve the six mental health indicators of the participants. Males’ self-awareness and decision-making actions were more positively affected than females. (4) Conclusions: The study helps to provide a path of establishing the mental health module of drama therapy in the education sector in Taiwan.